Combining nanostructuration with boron doping to alter sub band gap acceptor states in diamond materials. Issue 34 (16th August 2018) - Choudhury, Sneha; Kiendl, Benjamin; Ren, Jian; Gao, Fang; Knittel, Peter; Nebel, Christoph; Venerosy, Amélie; Girard, Hugues; Arnault, Jean-Charles; Krueger, Anke; Larsson, Karin; Petit, Tristan
Abstract : Synergistic effect of nanostructuration and boron doping allows sub-bandgap electron acceptor states in diamond materials to be controlled. Abstract : Diamond is a promising metal-free photocatalyst for nitrogen and carbon dioxide reduction in aqueous environment owing to the possibility of emitting highly reducing solvated electrons. However, the wide band gap of diamond necessitates the use of deep UV to trigger a photochemical reaction. Boron doping introduces acceptor levels within the band gap of diamonds, which may facilitate visible-light absorption through defect-based transitions. In this work, unoccupied electronic states from different boron-doped diamond materials, including single crystal, polycrystalline film, diamond foam, and nanodiamonds were probed by soft X-ray absorption spectroscopy at the carbon K edge. Supported by density functional theory calculations, we demonstrate that boron close to the surfaces of diamond crystallites induce acceptor levels in the band gap, which are dependent on the diamond morphology. Combining boron-doping with morphology engineering, this work thus demonstrates that electron acceptor states within the diamond band gap can be controlled.